PENGARUH WAKTU PEMERAMAN TERHADAP UJI KUAT TEKAN PAVING BLOCK DARI CAMPURAN TANAH, SEMEN DAN PASIR MENGGUNAKAN ALAT PENETRASI MODIFIKASI MODIFIKASI - prabowo, prasetio putro; setyanto, setyanto; adha, idharmahadi (Jurnal Rekayasa Sipil dan Desain (JRSDD), 2017)
AbstractPaving blocks are compositions of building material constructed from a mixture of Portlandcement or other similar hydrolysis, water, and aggregate or without other additives which do notruduce the quality of the material. In this research, the process of making paving blocks using amodified penetration tool in oder to improve the paving blocks quality in accordance with SNI-03-0691-1996. The soil samples tested from Kota Baru, Lampung Selatan. The amount of mixturepaving blocks was 75% of soil, 10% of sand and 15% of cement. The variation of curing time were0 days. 7 days, 14 days and 28 days as well as with pre and post burning treatment on the pavingblocks samples. The result showed that the making of paving blocks using silt with additionalmaterial of cement and sand fulfill the requirement in SNI-03-0691-1996. The addition and thecuring done could improve the physical and mechanical properties of the soil. For thecompressive strength value of the paving blocks with or without burning treatment, the best resultis shown in addition of 75% soil, 10% of sand and 15% of cement with 14 days curing time whichfulfill the requirement in SNI-03-0691-1996. The result of water absorption value which wasbetween 20,7% - 24,2% did not meet the specification in SNI-03-0691, 1996 that is 3% - 10%.Keywords : paving block, silt, compressive strength, curing time, water absorption.